Architectural and Planning Features of Derna (Central Region) - الشمري, د.ناصر; حسين, عبدالرحيم (Journal of Planner and Development, 2007)
The city of Derna has distinctive architectural and architectural features, like other Arab and Islamic cities in the Arab West and North Africa. Its markets and shops have taken many different forms and structural forms within the urban fabric of the central commercial zone. The meeting between the various commercial and handicraft jobs and consumers within a spatial area starting with the old markets of the dark market and the agency of the harvest and vegetable market and the mosque of the old and the square of the mosque and the Red Square and the square Kharazin. It then grew linearly towards commercial hubs that were associated with the city's expansion axes. Old markets represent the architectural and planning heritage associated with local economic, social and environmental influences. This phenomenon has been closely linked to the commercial dimension of the city with its demographic and spatial dimensions. And reflects the extent of their relevance and influence in the development of the pattern of urbanization and development from the dense and compact to the linear line and then to use the third dimension with the development and growth of the urban city and its commercial institutions that took the important role and active in the Arab and Islamic city of the Islamic principles of respect for business. The central commercial district of Darnah took its distinctive features from the other regions, as it required the provision of axes for the movement of the shopkeepers to obtain their needs from the required commercial jobs such as markets, artisans shops and technicians for the residents of the city and the area of ​​the impact of its commercial and marketing activities. A distinctive feature of the city, like other Arab Islamic cities, is the presence of patterns from the markets such as minors, agencies, markets of narrow alleys and the axis of the Najjar. The research deals with the most important characteristics and characteristics that characterized the city from the other and identified their features and distinctive features